Pembelajaran Pendidikan Inklusif Pada Sekolah Penyelenggara Pendidikan Inklusif - Wiwi Purnama Dewi; Sudadio Sudadio; Nurul Anriani (Journal on Education, 2024)
The background to writing this article is that there are children with special needs who should have the same rights in obtaining education as students in general at school. Inclusive education provided in schools providing inclusive education must be well prepared, especially learning that is adapted to the conditions of students with special needs. Children with special needs will study together with students in general in regular classes at schools providing inclusive education. Learning is structured by considering the conditions of students in class and the adjustments of other students in regular classes. The author conducted a literature study based on the results of previous research on the topic of inclusive education. The author states that to implement an inclusive education system, the principle thing that cannot be avoided is to carry out the process of developing inclusive education learning components in Inclusive Education Organizing Schools (SPPI). The learning components of inclusive education include: planning, implementing and evaluating inclusive education. SPPI must embody inclusive principles starting from planning, implementation processes, monitoring or supervision, to evaluation and preparation of follow-up plans for implementing school programs. SPPI also organizes the PPI (Individual Learning Program) program assisted by special supervising teachers outside regular class learning hours.